2020
DOI: 10.1177/2167702620923649
|View full text |Cite
|
Sign up to set email alerts
|

Low Emotional Awareness as a Transdiagnostic Mechanism Underlying Psychopathology in Adolescence

Abstract: The ability to identify and label one’s emotions is associated with effective emotion regulation, rendering emotional awareness important for mental health. We evaluated how emotional awareness was related to psychopathology and whether low emotional awareness was a transdiagnostic mechanism explaining the increase in psychopathology during the transition to adolescence and as a function of childhood trauma—specifically, violence exposure. In Study 1, children and adolescents ( N = 120, age range = 7–19 years)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 115 publications
1
37
0
2
Order By: Relevance
“…Prior work on factors that confer vulnerability or protection to stress-related psychopathology have primarily focused on cognitive, neurobiological, and social factors (Alloy et al, 1999; Cheng et al, 2014; Cohen, 2004; Dennison et al, 2016; Hooley et al, 2009; Hooley & Gotlib, 2000; Nikolova et al, 2012; Russo et al, 2012; Swartz et al, 2015). However, recent studies have revealed that aspects of emotion understanding may shape stress responding and the development of psychopathology (Armstrong et al, 2011; Kranzler et al, 2016; Nook & Somerville, 2020; Southam-Gerow & Kendall, 2002; Weissman et al, 2020). Here, we extend this body of knowledge by showing that emotion differentiation in particular moderates the link between stress and internalizing problems in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on factors that confer vulnerability or protection to stress-related psychopathology have primarily focused on cognitive, neurobiological, and social factors (Alloy et al, 1999; Cheng et al, 2014; Cohen, 2004; Dennison et al, 2016; Hooley et al, 2009; Hooley & Gotlib, 2000; Nikolova et al, 2012; Russo et al, 2012; Swartz et al, 2015). However, recent studies have revealed that aspects of emotion understanding may shape stress responding and the development of psychopathology (Armstrong et al, 2011; Kranzler et al, 2016; Nook & Somerville, 2020; Southam-Gerow & Kendall, 2002; Weissman et al, 2020). Here, we extend this body of knowledge by showing that emotion differentiation in particular moderates the link between stress and internalizing problems in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and three participants were enrolled in a broader study of emotional development (see Nook, Sasse, Lambert, McLaughlin, & Somerville, 2017; Nook, Sasse, Lambert, McLaughlin, & Somerville, 2018; Nook et al., 2019; Weissman et al, in press). Data from 11 participants were unusable and thus excluded (two did not complete the task, seven did not understand and/or cooperate with instructions, two experienced technical problems).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is possible that emotion recognition and regulation difficulties of comorbid psychopathology seen in patients with ASD (Aldao et al, 2010; McLaughlin & Nolen-Hoeksema, 2011; Weissman et al, 2019) are associated with alexithymia (Bilotta et al, 2016; Laloyaux et al, 2015). In addition, high levels of autistic traits have similarly been associated with altered emotion processing (Corden et al, 2008; Samson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%